2019
DOI: 10.1186/s12933-019-0842-0
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular concentric geometry predicts incident diabetes mellitus independent of established risk factors in the general population: the Copenhagen City Heart Study

Abstract: BackgroundSubtle impairments in left ventricular (LV) function and geometry are common findings in individuals with diabetes. However, whether these impairments precede the development of diabetes mellitus (DM) is not entirely clear.MethodsEchocardiograms from 1710 individuals from the general population free of prevalent diabetes mellitus were analyzed. Left ventricular (LV) concentric geometry was defined as either LV concentric remodeling or LV concentric hypertrophy as directed in contemporary guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…The same study reported that mild, moderate and severe heart failure was associated with 34%, 63%, and 68% increased risk of incident DM, respectively. Findings from other studies also concur with the results of the current study, showing that CVD signi cantly increases the risk of incident DM [6,21].…”
Section: Discussionsupporting
confidence: 92%
“…The same study reported that mild, moderate and severe heart failure was associated with 34%, 63%, and 68% increased risk of incident DM, respectively. Findings from other studies also concur with the results of the current study, showing that CVD signi cantly increases the risk of incident DM [6,21].…”
Section: Discussionsupporting
confidence: 92%
“…The same study reported that mild, moderate and severe heart failure was associated with 34%, 63%, and 68% increased risk of incident DM, respectively. Findings from other studies also concur with the results of the current study, showing that CVD signi cantly increases the risk of incident DM [6,21].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, left ventricular geometry remodeling in the general population can be referred to as a possible risk factor for incident diabetes mellitus, this was suggested by Modin et al in their study on 1710 individuals from the general population free of diabetes mellitus where they found in a multivariable model after adjusting for established DM risk factors such as HbA1c, BMI and plasma glucose, LV concentric geometry and RWT remained significantly associated with incident DM (LV concentric geometry: hazard ratio (HR) 1.99, 95% CI 1.11-3.57, p = 0.021) (RWT: HR 1.41, 95% CI 1.06-1.86, p = 0.017, per 0.1 increase) [25].…”
Section: Discussionmentioning
confidence: 97%